2018
DOI: 10.1519/jsc.0000000000002433
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Versus Suspended Push-up Muscle Activation in Athletes and Sedentary Women

Abstract: Syed-Abdul, MM, Soni, DS, Miller, WM, Johnson, RJ, Barnes, JT, Pujol, TJ, and Wagganer, JD. Traditional versus suspended push-up muscle activation in athletes and sedentary women. J Strength Cond Res 32(7): 1816-1820, 2018-Many strength training programs incorporate push-up exercises, which primarily activate upper-body muscles. Past data support the fact that shoulder girdle muscles (i.e., triceps (T) and anterior deltoids [AD]) exhibit greater electromyography (EMG) activity when a push-up is performed on an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 12 publications
2
24
0
Order By: Relevance
“…Following the screening of titles and abstracts, 80 full-text articles were subjected to detailed evaluation. Finally, 28 articles were recognized as eligible studies for inclusion ( 1 , 4 , 21 , 51 75 ) ( Figure 1 ). For the meta-analysis, 5 studies out of 28 eligible studies were excluded ( 1 , 56 , 60 , 68 , 72 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the screening of titles and abstracts, 80 full-text articles were subjected to detailed evaluation. Finally, 28 articles were recognized as eligible studies for inclusion ( 1 , 4 , 21 , 51 75 ) ( Figure 1 ). For the meta-analysis, 5 studies out of 28 eligible studies were excluded ( 1 , 56 , 60 , 68 , 72 ).…”
Section: Resultsmentioning
confidence: 99%
“…Upper limb training programs are commonly employed to increase stability, strength, and mobility while reducing the risk of injury ( 1 ). To select the most ideal exercises, Karandikar and Vargas ( 2 ) compared the concepts and clinical applications of open and closed kinetic chain exercises and concluded that a comprehensive training program should encompass a combination of these two types of exercises ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of studies with insufficient data or which only presented the results in graphs, the authors were contacted by email or Research Gate to allow their inclusion in the review. Some studies presented mean values and standard errors, making it not possible to include the results in the meta-analysis [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Therefore, in some cases, it was necessary to transform the standard error values into standard deviations using Review Manager 5.3 (The Cochrane Collaboration, Copenhagen, Denmark) to include these results in the meta-analysis [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…Some studies presented mean values and standard errors, making it not possible to include the results in the meta-analysis [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Therefore, in some cases, it was necessary to transform the standard error values into standard deviations using Review Manager 5.3 (The Cochrane Collaboration, Copenhagen, Denmark) to include these results in the meta-analysis [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. The authors were contacted for further information if the paper did not provide enough data.…”
Section: Methodsmentioning
confidence: 99%
“…In knuckle push-up, both fists will be clenched, while in a regular push-up, the palm is stretched open, touching the floor. This variance leads to a different muscle activation [8] and also a different risk of injury. From comparing the loads on the elbow, it was claimed that knuckle push-up resulting in a larger value than regular push-up (0.35BW ± 0.02 > 0.2BW ± 0.04) [9,10].…”
Section: Introductionmentioning
confidence: 99%